Are patients on basal insulin attaining glycemic targets? Characteristics and goal achievement of patients with type 2 diabetes mellitus treated with basal insulin and physician-perceived barriers to achieving glycemic targets. (November 2016) - Dalal, Mehul R.; Grabner, Michael; Bonine, Nicole; Stephenson, Judith J.; DiGenio, Andres; Bieszk, Nella
Highlights: In this real-world retrospective analysis 27% of insulin treated T2D patients reached HbA1c < 7%. Through survey, physicians identified practice philosophy regarding patients on insulin. Costs, patient's lifestyle and adherence were the main barriers to intensification by physicians. Fear of hypoglycemia and weight changes were considered to be less important by physicians. Abstract: Aims: To investigate treatment patterns and achievement of glycemic targets in patients with type 2 diabetes mellitus treated with basal insulin in a real-world setting, and to determine physicians' beliefs and practices regarding these patients. Methods: This study had two components; a retrospective analysis using a US claims database of patient and treatment data, and a survey of physicians' beliefs and practices. Results: A total of 39, 074 patients treated with basal insulin were included in this analysis. The proportion of patients achieving HbA1c < 7.0% (53 mmol/mol) was similar in ongoing basal insulin users at baseline (26%) and at 3 months follow-up (27%). The number of new initiators achieving HbA1c < 7.0% (53 mmol/mol) increased from baseline (11%) to 3 months (27%). In the physician survey component, the majority of physicians indicated they would continue to increase basal insulin dose as long as was needed to reach HbA1c/fasting blood glucose goals (85% of physicians treating 'not on-goal' patients, 78% of physicians treating 'on-goal' patients). Physician-perceived barriers to insulin intensification included patient's lifestyle, non-adherence, and concerns about out-of-pocket costs. Conclusions: A large proportion of patients on insulin-based therapy fail to reach glycemic goals. More education of clinicians may improve insulin intensification rates and increase the proportion of patients reaching glycemic targets.